Psychological Treatment of Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Three children, ages 12-15, with frequent refractory seizures were treated by behavioral intervention techniques in the Depts of Medical Rehabilitation and Clinical Neurophysiology, Orebro Medical Center Hospital, Orebro, and Dept of Clinical Psychology, University of Uppsala, Sweden.